image/con/text Dokumentarische Praktiken zwischen Journalismus, Kunst und Aktivismus - Fromm, Karen; Greiff, Sophia; Radtki, Malte; Stemmler, Anna (Reimer Verlag, 2020)
In photo books, but also in film, multimedia, and comics, current journalistic and artistic narrative forms open up new perspectives for the field of photojournalism and documentary photography that expand the view beyond the boundaries of the conventional understanding of the documentary form. They emphasize the contextuality of photography by focusing on the complementarity of witnessing and show that meaning can only be developed in the complex interplay of images, texts, and documents. The strategies considered in this volume move between journalistic, artistic, and activist positions, interweaving fact and fiction and tracing constellations of power in the process of representation.